Potential use of saline resources for biofuel production using halophytes and marine algae: prospects and pitfalls - Abideen, Zainul; Ansari, Raziuddin; Hasnain, Maria; Flowers, Timothy J.; Koyro, Hans-Werner; El-Keblawy, Ali; Abouleish, Mohamed; Khan, Muhammed Ajmal (Frontiers in Plant Science, 2023)
There exists a global challenge of feeding the growing human population of the world and supplying its energy needs without exhausting global resources. This challenge includes the competition for biomass between food and fuel production. The aim of this paper is to review to what extent the biomass of plants growing under hostile conditions and on marginal lands could ease that competition. Biomass from salt-tolerant algae and halophytes has shown potential for bioenergy production on salt-affected soils. Halophytes and algae could provide a bio-based source for lignoceelusic biomass and fatty acids or an alternative for edible biomass currently produced using fresh water and agricultural lands. The present paper provides an overview of the opportunities and challenges in the development of alternative fuels from halophytes and algae. Halophytes grown on marginal and degraded lands using saline water offer an additional material for commercial-scale biofuel production, especially bioethanol. At the same time, suitable strains of microalgae cultured under saline conditions can be a particularly good source of biodiesel, although the efficiency of their mass-scale biomass production is still a concern in relation to environmental protection. This review summaries the pitfalls and precautions for producing biomass in a way that limits environmental hazards and harms for coastal ecosystems. Some new algal and halophytic species with great potential as sources of bioenergy are highlighted.